Educational Gender Gaps - Shelly Lundberg (Institute of Labor Economics (IZA), 2020)
Cross-country studies reveal two consistent gender gaps in education—underachievement in school by boys and low rates of participation in STEM studies by girls. Recent economics research has shown the importance of social influences on women's STEM avoidance, but male low achievement has been less-studied and tends to be attributed to behavior problems and deficient non-cognitive skills. I revisit the determinants of the gender gap in U.S. educational attainment with a relatively-advantaged sample of young men and women and find that school behavior and measured skills are not very important drivers of gender differences, particularly in the transition to college. Educational aspirations, on the other hand, are strongly predictive of educational gaps and the gender difference in aspirations cannot be explained, even with rich adolescent data that includes parental expectations and school achievement indicators. These results suggest that gender identity concerns may influence (and damage) the educational prospects of boys as well as girls through norms of masculinity that discourage academic achievement.
Keywords: I20; J12; J16; 330; education; gender identity; school achievement; gender; aspirations; college graduation